(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2023)
Nowadays higher education institutions are directly involved in the training of new personnel, so they should seriously puzzle one of the most obvious questions today, how to prepare students to meet the challenges of Industrial Revolution 4.0 in an increasingly globalised society. And although the unequivocal answer to this question doesn’t exist, one thing is certain: while providing Education 4.0 through incorporating advanced technology into the curriculum for implementing best practices and innovative methodological approaches, methods and techniques, higher education institutions should do their best to shape the next generation of highly employable global citizens who can think and act from a global perspective. In the future students who specialise in the field of Computer Engineering and Information Technology will be at the forefront of advancing the technology available to all people in the world and, therefore, they should be globally competent. It means that they should possess a global competence to successfully compete on a global scale. Significant practical experience gained by the authors of the article made it possible to assume that being one of the humanities which is taught to Computer Engineering and Information Technology undergraduates in Ukrainian higher education institutions, English has a great potential for developing their global competence. Considering the fact that Ukrainian 15-year-old students were not a part of the PISA 2018 Global Competence assessment, the present research was aimed at finding out how the participants understood the concept of “global competence”, their awareness of the importance of global competence development in accordance with the requirements and principles of Education 4.0 associated with the Industrial Revolution 4.0 and participants’ views on the role of the English language in its development. For exactly this purpose the authors made a questionnaire in Google Forms. The research participants were 249 Computer Engineering and Information Technology undergraduates who were selected by means of a purposeful sampling method. The conducted research shows that the didactic uniqueness of the English language as an academic discipline aimed at developing global competence is manifested in the fact that it can be seen as both a learning goal and a learning tool. The results obtained became the basis for devising a paradigm defining strategy (the core strategy) and four sub-strategies effective for developing Computer Engineering and Information Technology undergraduates’ global competence in the English language classroom.